Three-dimensional porous heating electrode, preparation method thereof and lithium iron phosphate battery
Patent Information
- Application Number
- CN202611174144.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-04
- Publication Date
- 2026-10-13
AI Technical Summary
对低温性能的改善可以从材料端、结构端分别进行,理论上降低材料的粒径、使用低温电解液均可以提升低温性能,但是当前铁锂材料基本均进行了纳米化、碳包覆,但是低温性能还需要进一步改善;使用低温电解液会提升低温性能但是一般会带来高温性能和寿命等性能的劣化
(1)本发明提出的三维多孔加热电极,可作为电池隔膜使用,可以在电池极卷中随机放置,起到“加热+绝缘隔离+离子传导”的三重作用,其核心结构包括三维多孔并具有通孔的泡沫镍片、充分浸润填充于泡沫镍片上的聚合物固态电解质层,以及与泡沫镍片连接并引出电芯外的一对极耳,配套设置外接电路及电路上的温控装置、限流电阻,各部件协同作用,确保加热安全、高效、可控。
Smart Images

Figure CN122907596A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of lithium batteries, specifically to a three-dimensional porous heating electrode, its preparation method, and a lithium iron phosphate battery. Background Technology
[0002] With the widespread application of new energy technologies in mobile electronic devices and electric vehicles, higher requirements are being placed on the performance of secondary batteries, such as fast charging, energy density, and low-temperature performance. Lithium iron phosphate (LFP) batteries, in particular, have poor low-temperature performance, which significantly limits their application in new energy vehicles. Improving low-temperature performance can be achieved through both material and structural improvements. Theoretically, reducing the particle size of materials and using low-temperature electrolytes can enhance low-temperature performance. However, current LFP materials are mostly nano-sized and carbon-coated, yet their low-temperature performance still requires further improvement. Using low-temperature electrolytes improves low-temperature performance but generally leads to degradation in high-temperature performance and battery life. At the structural end, heating materials such as nickel foil and MOS films can be used inside or on the battery casing. For example, in patent CN 108987795, NTC ceramic oxide material is filled into a porous current collector. This utilizes the high internal resistance at low temperatures to generate heat and raise the battery temperature. However, at extremely low temperatures (-20°C), the resistance spikes, resulting in almost no conductivity and no heat generation, rendering the self-heating insulation method completely ineffective. The NTC resistance only decreases after the battery itself releases heat and heats up, but by then the low-temperature start-up phase has been missed. When the temperature rises, the resistance drops sharply, leading to uneven current distribution in certain areas. Patent CN104659332 uses nickel foam as a current collector to improve battery rate performance, mainly by utilizing the high porosity of nickel foam to store active materials and improve electrolyte wetting. However, this design affects the compaction calculation, thus impacting the battery's electrical performance.
[0003] Based on this technical background, this invention studies a three-dimensional porous heating electrode, its preparation method, and a lithium iron phosphate battery. Summary of the Invention
[0004] To address the shortcomings of existing technologies, this invention provides a three-dimensional porous heating electrode, its preparation method, and a lithium iron phosphate battery. The heating electrode as a whole can be used as a battery separator and can be randomly placed in the battery electrode roll, playing a triple role of "heating + insulation and isolation + ion conduction". Its core structure includes a three-dimensional porous nickel foam sheet with through holes, a polymer solid electrolyte layer fully impregnated and filled on the nickel foam sheet, and a pair of tabs connected to the nickel foam sheet and led out of the battery cell. It is equipped with an external circuit and a temperature control device and a current limiting resistor on the circuit. All components work together to ensure that the heating is safe, efficient, and controllable.
[0005] To achieve the above objectives, a first aspect of the present invention provides a three-dimensional porous heating electrode, comprising: Nickel foam sheets have a three-dimensional porous and through-hole structure; A polymer solid electrolyte layer is filled and composited on the surface and internal pores of the nickel foam sheet to isolate electrons and conduct ions, while also achieving insulation between the nickel foam sheet and the positive and negative electrode sheets of the battery. A pair of tabs, located outside the battery cell, are integrally formed with the nickel foam sheet and include a positive tab and a negative tab; An external circuit, located outside the battery cell and electrically connected to the pair of tabs, includes a temperature control device and a current-limiting resistor, used to provide heating current to the nickel foam sheet and to achieve safety protection and precise control of the heating process.
[0006] A second aspect of the present invention provides a method for preparing the heating electrode described in the first aspect, comprising: Pretreatment of nickel foam sheets: Select nickel foam sheets and perform cutting, trimming, cleaning, drying, cooling, and optional surface activation treatment in sequence; Preparation of polymer solid electrolyte slurry: Using a high molecular polymer as the matrix, lithium salt and nano-inorganic insulating filler are doped, and the polymer solid electrolyte slurry is obtained by solvent dissolution, dispersion and settling in sequence. Preparation of heating electrodes: A polymer solid electrolyte slurry was coated onto the surface and inner walls of the pores of a pretreated nickel foam sheet using a solution casting method, ensuring that the slurry completely wetted all the pores of the nickel foam sheet. Then, the sheet was sequentially subjected to ventilation pre-drying, segmented drying and curing, and isothermal curing to obtain the polymer solid electrolyte layer. A third aspect of the present invention provides a lithium iron phosphate battery, characterized in that the lithium iron phosphate battery includes the heating electrode described in the first aspect, or a heating electrode prepared by the preparation method of the second aspect.
[0007] The beneficial effects of this invention include: (1) The three-dimensional porous heating electrode proposed in this invention can be used as a battery separator. It can be randomly placed in the battery electrode roll and plays a triple role of "heating + insulation and isolation + ion conduction". Its core structure includes a three-dimensional porous nickel foam sheet with through holes, a polymer solid electrolyte layer fully wetted and filled on the nickel foam sheet, and a pair of tabs connected to the nickel foam sheet and led out of the battery cell. It is equipped with an external circuit and a temperature control device and a current limiting resistor on the circuit. All components work together to ensure that the heating is safe, efficient and controllable.
[0008] (2) The three-dimensional porous heating electrode proposed in this invention has a three-dimensional porous structure with through holes. Compared with traditional planar resistive sheets, it has a large specific surface area and excellent conductivity. It can make the current evenly distributed on the entire nickel sheet surface, achieve uniform heat generation, high heating efficiency, and meet the low-temperature heating requirements of batteries.
[0009] (3) The three-dimensional porous heating electrode proposed in this invention has strong structural adaptability. The three-dimensional porous structure of the nickel foam sheet has good flexibility and adaptability, and can be designed to fit the shape of the battery electrode sheet. It does not need to occupy too much internal space of the battery, and avoids the decrease in battery energy density due to the excessive size of the heating component. The solid electrolyte membrane has excellent thermal stability and will not cause internal shorting due to thermal shrinkage of the separator after heating.
[0010] Other features and advantages of the present invention will be described in detail in the following detailed description section. Attached Figure Description
[0011] The above and other objects, features and advantages of the present invention will become more apparent from the more detailed description of exemplary embodiments of the invention in conjunction with the accompanying drawings.
[0012] Figure 1 This is a schematic diagram showing the structure of the three-dimensional porous heating electrode proposed in this invention and its placement in a battery. Detailed Implementation
[0013] Preferred embodiments of the invention will now be described in more detail. While preferred embodiments of the invention are described below, it should be understood that the invention can be implemented in various forms and should not be limited to the embodiments set forth herein.
[0014] This invention provides a three-dimensional porous heating electrode, such as... Figure 1 As shown, it includes: Nickel foam sheets have a three-dimensional porous and through-hole structure; A polymer solid electrolyte layer is filled and composited on the surface and internal pores of the nickel foam sheet to isolate electrons and conduct ions, while also achieving insulation between the nickel foam sheet and the positive and negative electrode sheets of the battery. A pair of tabs, located outside the battery cell, are integrally formed with the nickel foam sheet and include a positive tab and a negative tab; The external circuit, located outside the battery cell and electrically connected to a pair of tabs, includes a temperature control device and a current-limiting resistor. It is used to provide heating current to the nickel foam sheet and to achieve safety protection and precise control of the heating process.
[0015] The three-dimensional porous heating electrode of this invention can be used as a battery separator. It can be randomly placed in the battery electrode roll and plays a triple role of "heating + insulation and isolation + ion conduction". Its core structure includes a three-dimensional porous nickel foam sheet with through holes, a polymer solid electrolyte layer fully impregnated and filled on the nickel foam sheet, and a pair of tabs connected to the nickel foam sheet and led out of the battery cell. It is equipped with an external circuit and a temperature control device and a current limiting resistor on the circuit. All components work together to ensure that the heating is safe, efficient and controllable.
[0016] According to the present invention, the porosity of the nickel foam sheet is 30% to 80%, preferably 40% to 60%. This porosity range is used to ensure that the nickel foam sheet has excellent electrical conductivity and heat generation efficiency, while providing sufficient space for the filling and composite of the polymer solid electrolyte layer, and taking into account the mechanical strength of the nickel foam sheet, so as to avoid structural damage due to excessive porosity. The porosity of the nickel foam sheet is greater than 95%. This porosity range is used to improve ion conduction efficiency while ensuring that heat can be quickly diffused through the pores, avoiding local heat accumulation.
[0017] According to the present invention, the thickness of the nickel foam sheet is 10~50μm, preferably 20~40μm; The length and width of the nickel foam sheet are both 2-3mm smaller than the positive electrode sheet of the battery, and it is designed to fit the shape of the battery electrode sheet. It is evenly distributed in the middle of the battery electrode sheet to avoid the risk of short circuit caused by the nickel foam sheet contacting the edges of the positive and negative electrode sheets of the battery. At the same time, it ensures that the nickel foam sheet generates heat evenly, eliminates local heat concentration, and prevents damage to the active material of the battery electrode sheet due to local overheating, which would affect the battery life and safety. A pair of tabs are led out through the battery explosion-proof valve to the external circuit. When a closed loop is formed, current flows through the nickel foam sheet to achieve the heating function.
[0018] In this invention, the solid electrolyte needs to completely fill the pores of the foamed nickel sheet and needs to exceed the nickel sheet by a certain thickness. Filling the pores can reduce the interfacial impedance. The solid electrolyte on the surface of the nickel sheet needs to have a certain thickness to ensure sufficient insulation and avoid safety issues. The length and width of the nickel foil need to be 2-3 mm less than the positive electrode sheet. The heating element needs to fit the shape of the battery electrode sheet and be evenly distributed in the middle of the electrode sheet to avoid local heat concentration.
[0019] In this invention, the three-dimensional porous heating electrode has a three-dimensional porous structure with through holes. Compared with traditional planar resistive sheets, it has a large specific surface area and excellent conductivity. It can make the current evenly distributed on the entire nickel sheet surface, achieve uniform heat generation, high heating efficiency, and meet the low-temperature heating requirements of batteries.
[0020] According to the present invention, the polymer solid electrolyte layer is a continuous and dense solid film formed by dissolving, dispersing, impregnating and curing a solvent with a high molecular polymer as the matrix and doping with lithium salt and nano-inorganic insulating filler. In the polymer solid electrolyte layer, based on the total mass of the polymer solid electrolyte, the content of the polymer matrix is 65-85%, the content of lithium salt is 5-15%, and the content of nano-inorganic insulating filler is 10-25%. The polymer matrix is selected from at least one of polyvinylidene fluoride-hexafluoropropylene copolymer (PVDF-HFP), polyethylene oxide (PEO), polymethyl methacrylate (PMMA) and polyacrylonitrile (PAN) to make the polymer solid electrolyte layer have good film-forming properties, high flexibility and strong adhesion to the foamed nickel sheet; The lithium salt is selected from at least one of lithium bis(trifluoromethanesulfonyl)imide (LiTFSI), lithium tetrafluoroborate (LiBF4), lithium hexafluorophosphate (LiPF6), and lithium perchlorate (LiClO4) to improve the polymer chain structure and enhance the compactness and ion conductivity of the polymer solid electrolyte layer. The nano-inorganic insulating filler is selected from at least one of nano-alumina (Al2O3), nano-silica (SiO2), boron nitride (BN) and nano-titanium dioxide (TiO2), with a particle size of 20-200 nm. It is used to improve the insulation withstand voltage and heat resistance of the polymer solid electrolyte layer, suppress leakage current, prevent film breakdown, and reduce the coefficient of thermal expansion to avoid film cracking. The solvent is selected from at least one of N-methylpyrrolidone (NMP), acetone, and ethanol; The solid content of the polymer solid electrolyte slurry obtained after solvent dissolution is 10-20%, preferably 14-16%.
[0021] In this invention, if the slurry has too low a solid content: it is too thin, resulting in poor wall adhesion, inability to coat the inner wall of the through holes, and insufficient insulation due to a thin film; if the solid content is too high: the viscosity is too high, making it difficult to wet the through holes of the nickel foam, leading to clogging and excessive buildup on the surface.
[0022] According to the present invention, the polymer is polyvinylidene fluoride-hexafluoropropylene copolymer, the lithium salt is lithium bis(trifluoromethanesulfonyl)imide, and the nano-inorganic insulating filler is nano-alumina. In the polymer solid electrolyte layer, based on the total mass of the polymer solid electrolyte, the content of polyvinylidene fluoride-hexafluoropropylene copolymer is 70-72%, the content of lithium bis(trifluoromethanesulfonyl)imide is 8-10%, and the content of nano-alumina is 19-21%.
[0023] According to the present invention, the total film thickness of the polymer solid electrolyte layer after curing is 10–50 μm, preferably 20–40 μm, and the volume resistivity is ≥10. 8 Ω·cm, breakdown voltage ≥500V, and structurally stable without cracking or detachment in an environment of -40℃~120℃, used to ensure that the battery maintains excellent insulation and ion conduction performance throughout its long-term use.
[0024] The three-dimensional porous heating electrode of the present invention has strong structural adaptability. The three-dimensional porous structure of the nickel foam sheet has good flexibility and adaptability, and can be designed to fit the shape of the battery electrode without occupying too much internal space of the battery, thus avoiding the decrease in battery energy density due to the excessive size of the heating component. The solid electrolyte membrane has excellent thermal stability and will not cause internal shorting due to thermal shrinkage of the separator after heating.
[0025] According to the present invention, the temperature control device forms a series circuit with the nickel foam sheet through a pair of tabs, and presets an upper temperature limit and a lower temperature limit for real-time monitoring of the external temperature of the battery. When the battery temperature is detected to reach the upper temperature limit, the series circuit is automatically cut off to stop heating the nickel foam sheet, thus avoiding thermal runaway and damage to the active material caused by excessive temperature. When the battery temperature is detected to be below the lower temperature limit, the series circuit is automatically activated to connect the current and make the nickel foam sheet start to generate heat, ensuring that the battery temperature is stable within the safe operating range and ensuring normal charging and discharging of the battery in low-temperature environments. The upper temperature limit is 50℃, and the lower temperature limit is 0℃. The current-limiting resistor forms a series circuit with the nickel foam sheet through a pair of tabs, serving as a protective element for abnormal conditions; When the nickel foam sheet experiences a short circuit and / or the polymer solid electrolyte layer is damaged, the current in the series circuit increases sharply. The series circuit is automatically cut off by the current-limiting resistor to limit the current from continuing to increase, prevent the fault from escalating, and prevent the battery from bulging, leaking, catching fire, or even exploding, thereby improving the safety and reliability of the heating electrode.
[0026] In this invention, the heating element has two pre-drilled tabs that extend to the outside of the battery cell. An external temperature control device and a current-limiting resistor are connected to the circuit. The temperature control device can monitor the battery temperature in real time. When the temperature reaches the preset upper limit, it automatically cuts off the external circuit current and stops heating. When the temperature is lower than the preset lower limit (such as in a low-temperature environment), it automatically starts heating to ensure that the battery temperature remains stable within a safe range. The current-limiting resistor can quickly cut off the circuit when the heating element experiences abnormalities such as short circuit or insulation layer damage, to prevent the fault from escalating and to prevent battery damage.
[0027] The present invention also improves a method for preparing the above-mentioned heating electrode, comprising: Pretreatment of nickel foam sheets: Select nickel foam sheets and perform cutting, trimming, cleaning, drying, cooling, and optional surface activation treatment in sequence; Preparation of polymer solid electrolyte slurry: Using a high molecular polymer as the matrix, lithium salt and nano-inorganic insulating filler are doped, and the polymer solid electrolyte slurry is obtained by solvent dissolution, dispersion and settling in sequence. Preparation of heating electrode: The polymer solid electrolyte slurry is coated on the surface and inner wall of the pores of the pretreated nickel foam sheet by solution casting, ensuring that the slurry completely wets all the pores of the nickel foam sheet. Then, ventilation pre-drying, segmented drying and curing and constant temperature curing are performed in sequence to obtain the heating electrode. Battery assembly: The positive electrode, separator and negative electrode are stacked in sequence, the heating electrode is encapsulated between the two negative electrode layers in the middle of the electrode core, and a pair of tabs are welded to the reserved tab positions on the battery cover plate. External circuit assembly: Connect the temperature control device, the current limiting resistor, and a pair of tabs in series to form an external closed circuit. Adjust the upper and lower temperature limits of the temperature control device and the current limiting parameters of the current limiting resistor to ensure that the circuit works normally.
[0028] According to the present invention, selecting nickel foam sheets and sequentially performing cutting, trimming, cleaning, drying, cooling, and surface activation treatments includes: Select nickel foam sheets with a thickness of 10~50μm, a porosity of 30%~80%, and a porosity greater than 95%, cut them according to the design dimensions, and trim them to fit the shape of the battery electrode to ensure that the length and width of the nickel foam sheets are 2~3mm smaller than the positive electrode sheet. The trimmed nickel foam sheets are ultrasonically cleaned in acetone, anhydrous ethanol and deionized water for 10-15 minutes each to remove surface oil and impurities. After drying at 80-120℃ for 1-2 hours and cooling naturally, plasma surface activation treatment is optionally performed for 1-3 minutes.
[0029] According to the present invention, a polymer solid electrolyte slurry is obtained by sequentially dissolving, dispersing, and settling a polymer as a matrix, doping it with lithium salt and nano-inorganic insulating filler, and then allowing it to stand. Add the polymer matrix to the solvent and stir at a constant temperature of 50-70°C for 3-6 hours until completely dissolved to form a transparent adhesive solution. Add lithium salt to the transparent adhesive solution, continue stirring at a constant temperature for 2-3 hours to mix thoroughly, then add nano-inorganic insulating filler, first mechanically stir for 25-35 minutes, then ultrasonically disperse for 30-60 minutes to eliminate filler agglomeration and obtain a uniform and stable slurry; The homogeneous and stable slurry was vacuum-degassed for 20-40 minutes to remove internal air bubbles, thus obtaining a polymer solid electrolyte slurry. The temperature for pre-drying is room temperature, and the time is 5 to 15 minutes; The temperature for segmented drying and curing is 60–80℃, and the time is 1–2 hours; The temperature for constant temperature curing is 110–130℃, and the time is 30–60 min; When the thickness of the obtained polymer solid electrolyte layer is less than 20 μm, repeat the steps of ventilation pre-drying, segmented drying and curing and constant temperature curing until the thickness of the cured polymer solid electrolyte layer reaches 20 μm and completely fills the pores of the nickel foam sheet.
[0030] The present invention also provides a lithium iron phosphate battery, which includes the heating electrode described above, or a heating electrode prepared by the preparation method described above.
[0031] The present invention will be described in more detail below through embodiments.
[0032] Example 1
[0033] like Figure 1 As shown, this embodiment provides a three-dimensional porous heating electrode, comprising: Nickel foam sheets have a three-dimensional porous and through-hole structure; A polymer solid electrolyte layer is filled and composited on the surface and internal pores of the nickel foam sheet to isolate electrons and conduct ions, while also achieving insulation between the nickel foam sheet and the positive and negative electrode sheets of the battery. A pair of tabs, located outside the battery cell, includes a positive tab and a negative tab, both of which are connected to a nickel foam sheet; The external circuit, located outside the battery cell and electrically connected to a pair of tabs, includes a temperature control device and a current-limiting resistor. It is used to provide heating current to the nickel foam sheet and to achieve safety protection and precise control of the heating process.
[0034] This embodiment provides a method for preparing three-dimensional porous structures, mainly including pretreatment of nickel foam sheets, preparation of polymer solid electrolyte slurry, casting and filling, curing, tab connection, and external circuit assembly. The specific steps are as follows: Step 1: Pretreatment of nickel foam sheet: Select nickel foam sheets with a thickness of 30μm, a porosity of 40%, and a porosity greater than 95%, cut them to the designed dimensions (length and width 2-3mm smaller than the positive electrode sheet), and trim them to fit the shape of the battery electrode sheet; ultrasonically clean them sequentially with acetone, anhydrous ethanol, and deionized water for 10-15 minutes each to remove surface oil and impurities; dry them in an oven at 80-120℃ for 1-2 hours, and allow them to cool naturally; optional plasma surface activation treatment for 1-3 minutes can be performed to improve the adhesion between the polymer solid electrolyte and the nickel foam sheet. Step 2, Preparation of Polymer Solid Electrolyte Slurry: Prepare an electrolyte slurry with a solid content of 14%. Add the PVDF-HFP matrix to NMP solvent and stir at 50-70℃ for 3-6 hours until completely dissolved to form a transparent solution. Add a measured amount of lithium salt LiPF6 to the solution and continue stirring at a constant temperature for 2-3 hours to mix thoroughly. Then add the nano-inorganic insulating filler Al2O3, first mechanically stir for 30 minutes, then ultrasonically disperse for 30-60 minutes to eliminate filler agglomeration and obtain a uniform and stable slurry. Vacuum stand the slurry for 20-40 minutes to remove internal bubbles and set aside for later use. Step 3: Preparation of heating element containing solid electrolyte membrane: Using solution casting, the polymer solid electrolyte slurry is coated onto the surface and inner walls of the pores of the pretreated nickel foam sheet, ensuring that the slurry completely wets all the pores of the nickel foam sheet; after coating, it is first pre-dried at room temperature for 5-15 minutes to allow the surface solvent to evaporate initially, and then dried and cured in stages: drying at 60-80℃ for 1-2 hours, and then heating to 110-130℃ for constant temperature curing for 30-60 minutes to obtain a continuous, dense, pinhole-free, and non-detachable polymer solid electrolyte layer. When the electrolyte layer thickness is less than 20μm, the casting and curing steps are repeated until the cured film thickness reaches 20μm and the electrolyte layer completely fills the pores of the nickel foam sheet and the surface thickness meets the insulation requirements; Step 4, Battery Assembly: Stack the positive electrode, separator and negative electrode in sequence, encapsulate the heating electrode between the two negative electrode layers in the middle of the electrode core, and weld the tab of the heating electrode to the reserved tab position of the special cover plate. Step 5: External circuit assembly: Connect the temperature control device, current limiting resistor, and tab lead-out terminal in series to form an external closed circuit. Adjust the upper and lower temperature limits of the temperature control device and the current limiting parameters of the current limiting resistor to ensure that the circuit works normally.
[0035] Example 2
[0036] Based on Example 1, an electrolyte slurry with a solid content of 16% was prepared. The slurry formulation was PEO+LiTFSI+SiO2, and the thickness of the resulting solid electrolyte layer was 40μm. Other aspects were the same as in Example 1.
[0037] Example 3
[0038] Based on Example 1, an electrolyte slurry with a solid content of 15% was prepared. The slurry formulation was PVDF-HFP:PEO=4:6, LiTFSI+SiO2. The thickness of the solid electrolyte layer obtained was 30μm, and the rest was the same as in Example 1.
[0039] Comparative Example 1
[0040] Use a 30μm thick nickel foam sheet with a porosity of 40% and a permeability greater than 95%. Do not coat the surface with polymer electrolyte insulation. Use a separator as the basic insulation. Assemble the battery and external circuit normally.
[0041] Comparative Example 2
[0042] Based on Example 1, the PVDF-HFP matrix slurry has a solid content of 8%, the thickness of the cured electrolyte membrane is 10 μm, and the rest is the same as in Example 1.
[0043] Comparative Example 3
[0044] Based on Example 2, the PEO matrix slurry has a solid content of 25%, the thickness of the cured electrolyte membrane is 30 μm, and the rest is the same as in Example 2.
[0045] Comparative Example 4
[0046] By using the heating electrode of Example 3, the temperature control device and current limiting resistor are eliminated, and an external power supply and switch are directly connected to achieve the function of heating when the power is on and not heating when the power is off.
[0047] Table 1. Comparison of the effects of Examples 1-3 and Comparative Examples 1-4 of this application.
[0048] As can be seen from Table 1, Embodiments 1-3 of the present invention, by coating the surface of the three-dimensional porous nickel foam and the inner wall of the through holes with a 20-40μm PVDF-HFP / PEO-based solid electrolyte insulating layer, and in conjunction with an external temperature control device and a current limiting resistor, not only achieve uniform heating inside the battery, but also ensure electrical insulation safety. The battery can automatically cut off power after reaching the set temperature, effectively avoiding the risks of short circuit and thermal runaway. In contrast, Comparative Examples 1-4, which lack an insulating layer, have an excessively thin insulating layer, have blocked through holes, or lack temperature control and current limiting protection, cannot simultaneously achieve safe heating and precise temperature control.
[0049] The various embodiments of the present invention have been described above. These descriptions are exemplary and not exhaustive, nor are they limited to the disclosed embodiments. Many modifications and variations will be apparent to those skilled in the art without departing from the scope and spirit of the described embodiments.
Claims
1. A three-dimensional porous heating electrode, characterized in that, include: Nickel foam sheets have a three-dimensional porous and through-hole structure; A polymer solid electrolyte layer is filled and composited on the surface and internal pores of the nickel foam sheet to isolate electrons and conduct ions, while also achieving insulation between the nickel foam sheet and the positive and negative electrode sheets of the battery. A pair of tabs, located outside the battery cell, are integrally formed with the nickel foam sheet and include a positive tab and a negative tab; An external circuit, located outside the battery cell and electrically connected to the pair of tabs, includes a temperature control device and a current-limiting resistor, used to provide heating current to the nickel foam sheet and to achieve safety protection and precise control of the heating process.
2. The heating electrode according to claim 1, characterized in that, The porosity of the nickel foam sheet is 30% to 80%, preferably 40% to 60%. This porosity range is used to ensure that the nickel foam sheet has excellent electrical conductivity and heat generation efficiency, while providing sufficient space for the filling and composite of the polymer solid electrolyte layer, and taking into account the mechanical strength of the nickel foam sheet to avoid structural damage due to excessive porosity. The porosity of the nickel foam sheet is greater than 95%. This porosity range is used to improve ion conduction efficiency while ensuring that heat can be quickly diffused through the pores to avoid local heat accumulation. The thickness of the nickel foam sheet is 10~50μm, preferably 20~40μm; The length and width of the foamed nickel sheet are both 2-3 mm smaller than the positive electrode sheet of the battery, and it is designed to fit the shape of the battery electrode sheet. It is evenly distributed in the middle of the battery electrode sheet to avoid the risk of short circuit caused by the foamed nickel sheet contacting the edges of the positive and negative electrode sheets of the battery. At the same time, it ensures that the foamed nickel sheet generates heat evenly, eliminates local heat concentration, and prevents damage to the active material of the battery electrode sheet due to local overheating, which would affect the battery life and safety. The pair of tabs are led out through the battery explosion-proof valve to the external circuit. When a closed loop is formed, current flows through the nickel foam sheet to achieve the heating function.
3. The heating electrode according to claim 1, characterized in that, The polymer solid electrolyte layer is a continuous and dense solid film formed by dissolving, dispersing, impregnating and curing a solvent with a high molecular polymer as the matrix and doping with lithium salt and nano-inorganic insulating filler. In the polymer solid electrolyte layer, based on the total mass of the polymer solid electrolyte, the content of the polymer matrix is 65-85%, the content of the lithium salt is 5-15%, and the content of the nano-inorganic insulating filler is 10-25%. The polymer is selected from at least one of polyvinylidene fluoride-hexafluoropropylene copolymer, polyethylene oxide, polymethyl methacrylate and polyacrylonitrile, and is used to make the polymer solid electrolyte layer have good film-forming properties, high flexibility and strong adhesion to the foamed nickel sheet; The lithium salt is selected from at least one of lithium bis(trifluoromethanesulfonyl)imide, lithium tetrafluoroborate, lithium hexafluorophosphate, and lithium perchlorate, and is used to improve the polymer chain structure and enhance the compactness and ion conductivity of the polymer solid electrolyte layer. The nano-inorganic insulating filler is selected from at least one of nano-alumina, nano-silica, boron nitride and nano-titanium dioxide, with a particle size of 20-200nm. It is used to improve the insulation and withstand voltage performance and heat resistance of the polymer solid electrolyte layer, suppress leakage current, prevent membrane breakdown, and reduce the coefficient of thermal expansion to avoid membrane cracking. The solvent is selected from at least one of N-methylpyrrolidone, acetone, and ethanol; The solid content of the polymer solid electrolyte slurry obtained after solvent dissolution is 10-20%, preferably 14-16%.
4. The heating electrode according to claim 3, characterized in that, The polymer is polyvinylidene fluoride-hexafluoropropylene copolymer, the lithium salt is lithium bis(trifluoromethanesulfonyl)imide, and the nano-inorganic insulating filler is nano-alumina. In the polymer solid electrolyte layer, based on the total mass of the polymer solid electrolyte, the content of the polyvinylidene fluoride-hexafluoropropylene copolymer is 70-72%, the content of lithium bis(trifluoromethanesulfonyl)imide is 8-10%, and the content of nano-alumina is 19-21%.
5. The heating electrode according to claim 1, characterized in that, The total film thickness of the polymer solid electrolyte layer after curing is 10–50 μm, preferably 20–40 μm, and the volume resistivity is ≥10. 8 Ω·cm, breakdown voltage ≥500V, and structurally stable without cracking or detachment in an environment of -40℃~120℃, used to ensure that the battery maintains excellent insulation and ion conduction performance throughout its long-term use.
6. The heating electrode according to claim 1, characterized in that, The temperature control device forms a series circuit with the nickel foam sheet through the pair of tabs, and presets an upper temperature limit and a lower temperature limit for real-time monitoring of the external temperature of the battery. When the battery temperature reaches the upper temperature limit, the series circuit is automatically cut off to stop heating the nickel foam sheet, thus preventing thermal runaway and damage to the active materials caused by excessive temperature. When the battery temperature is detected to be below the lower temperature limit, the series circuit is automatically activated to turn on the current and allow the nickel foam sheet to start generating heat, ensuring that the battery temperature remains stable within the safe operating range and guaranteeing normal charging and discharging of the battery in low-temperature environments. The upper temperature limit is 50°C, and the lower temperature limit is 0°C. The current-limiting resistor forms a series circuit with the nickel foam sheet through the pair of tabs, serving as a protective element for abnormal situations; When the foamed nickel sheet experiences a short circuit and / or the polymer solid electrolyte layer is damaged, the current in the series circuit increases sharply. The series circuit is automatically cut off by the current-limiting resistor, which limits the current from continuing to increase, prevents the fault from escalating, and prevents the battery from bulging, leaking, catching fire, or even exploding, thereby improving the safety and reliability of the heating electrode.
7. A method for preparing a heating electrode according to any one of claims 1-6, characterized in that, include: Pretreatment of nickel foam sheets; Select nickel foam sheets and perform cutting, trimming, cleaning, drying, cooling, and optional surface activation treatment in sequence; Preparation of polymer solid electrolyte slurry: Using a high molecular polymer as the matrix, lithium salt and nano-inorganic insulating filler are doped, and the polymer solid electrolyte slurry is obtained by solvent dissolution, dispersion and settling in sequence. Preparation of heating electrode: The polymer solid electrolyte slurry is coated on the surface and inner wall of the pores of the pretreated nickel foam sheet by solution casting, ensuring that the slurry completely wets all the pores of the nickel foam sheet. Then, ventilation pre-drying, segmented drying and curing and constant temperature curing are performed in sequence to obtain the heating electrode. Battery assembly: The positive electrode, separator and negative electrode are stacked in sequence, the heating electrode is encapsulated between the two negative electrode layers in the middle of the electrode core, and a pair of tabs are welded to the reserved tab positions on the battery cover plate. External circuit assembly: Connect the temperature control device, the current limiting resistor, and a pair of tabs in series to form an external closed circuit. Adjust the upper and lower temperature limits of the temperature control device and the current limiting parameters of the current limiting resistor to ensure that the circuit works normally.
8. The preparation method according to claim 7, characterized in that, Selected nickel foam sheets undergo a series of processes including cutting, trimming, cleaning, drying, cooling, and surface activation. Select a nickel foam sheet with a thickness of 10~50μm, a porosity of 30%~80%, and a through-pore rate of greater than 95%. Cut it according to the design size and trim it to fit the shape of the battery electrode to ensure that the length and width of the nickel foam sheet are 2~3mm smaller than the positive electrode sheet. The trimmed nickel foam sheet is ultrasonically cleaned with acetone, anhydrous ethanol and deionized water for 10-15 minutes each to remove surface oil and impurities. After drying at 80-120°C for 1-2 hours and naturally cooling, it is then optionally subjected to plasma surface activation treatment for 1-3 minutes.
9. The preparation method according to claim 7, characterized in that, Using a polymer matrix, doped with lithium salts and nano-inorganic insulating fillers, a polymer solid electrolyte slurry is obtained by sequentially dissolving, dispersing, and settling in a solvent, comprising: Add the polymer matrix to the solvent and stir at a constant temperature of 50-70°C for 3-6 hours until completely dissolved to form a transparent adhesive solution. Lithium salt was added to the transparent adhesive solution, and the mixture was stirred at a constant temperature for 2-3 hours to ensure thorough mixing. Then, nano-inorganic insulating filler was added, and the mixture was first mechanically stirred for 25-35 minutes, followed by ultrasonic dispersion for 30-60 minutes to eliminate filler agglomeration and obtain a uniform and stable slurry. The homogeneous and stable slurry was vacuum-degassed for 20-40 minutes to remove internal air bubbles, resulting in a polymer solid electrolyte slurry. The ventilation pre-drying temperature is room temperature, and the time is 5 to 15 minutes; The temperature for the segmented drying and curing is 60–80°C, and the time is 1–2 hours. The temperature for constant temperature curing is 110–130°C, and the time is 30–60 min; When the thickness of the obtained polymer solid electrolyte layer is less than 20 μm, repeat the steps of ventilation pre-drying, segmented drying and curing and constant temperature curing until the thickness of the cured polymer solid electrolyte layer reaches 20 μm and completely fills the pores of the nickel foam sheet.
10. A lithium iron phosphate battery, characterized in that, The lithium iron phosphate battery includes the heating electrode according to any one of claims 1 to 6, or the heating electrode prepared by any one of claims 7 to 9.